Improving student achievement through evaluation of volleyball training program: A case study at SMAN 1 Kadupandak - Yesty Yustianti Fratiwi; Akhmad Sobarna; Rony Mohamad Rizal (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aims to evaluate the effectiveness of the Volleyball Team Training Program at SMA Negeri 1 Kadupandak using the CIPP evaluation model, which encompasses context, input, process, and product. Context evaluation examines the alignment of program objectives with the school's vision and mission, while input evaluation covers the availability of human resources, facilities, and funding. Process evaluation focuses on training implementation, program management, and supervision, while product evaluation assesses program outcomes in the form of improved technical skills, character, and student achievement. This study used a descriptive approach with quantitative and qualitative methods. Data were collected through questionnaires, interviews, observation, and documentation. The results indicate that the volleyball training program was quite effective in improving student skills and resulting in achievements at the district and provincial levels. The program's objectives were deemed relevant to the school's vision, although socialization still needs improvement. Coach quality and student motivation are key strengths, but limited facilities, funding, and training schedule conflicts remain obstacles. Therefore, improvements in facilities, funding, and program coordination are recommended to enhance the sustainability and effectiveness of the training.